ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Basic Materials yang Terdaftar Di BEI Periode 2020-2023) - Rosyidani, Nabila Masithoh; Lintang Kurniawati (ITB AAS Indonesia Surakarta, 2025)
As economic entities, companies are not only oriented toward short-term profit attainment, but also aim to increase their long-term value by implementing Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR), especially in the basic materials sector, which has considerable environmental and social impacts. This study explores how GCG and CSR affect firm value in companies listed in the basic materials sector on the Indonesia Stock Exchange (IDX) from 2020 to 2023. GCG is represented by managerial ownership, board of directors, board of commissioners, and audit committee. Using a quantitative approach with explanatory research, the study relies on secondary data gathered from annual company reports. The sample was selected through purposive sampling and analyzed using multiple linear regression along with classical assumption tests. The results show that GCG and CSR together have a significant impact on firm value, but when tested individually, only the board of directors shows a significant effect, while the other variables do not show a significant impact on firm value.